A proposal method for fault detection and diagnosis in chemical processes instrumentation using wavelet transform - Guillén, Marcos; Paredes, José; Camacho, Oscar (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper presents an approach to analyse different kinds of chemical processes instrumentation faults. The proposed approach makes a detection and diagnosis of the instrument worsening in the process. A chemical process mode! is used to show how the approach works. to differentiate valves and transmitter problems an analysis in the wavelet domain is presented along with pattern recognition procedures. such as correlation coefficient and Euclidean distance approaches.